Effectiveness of Integrated Waste Management Program by Waste Management Institution - Syakira Az Zahra; Rizki Syafril (Journal of Educational Management Research, 2025)
This study aims to analyze the effectiveness of the Integrated Waste Management Program by the Waste Management Institution in Balai Gadang Village as an effort to reduce waste from its source. Although this program has been implemented, there are still obstacles in its implementation that hinder the effectiveness of the program. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of the Waste Management Institution of Balai Gadang Village and the Padang City Environmental Agency. The data analysis process is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Integrated Waste Management Program has not been running effectively, because several problems are still found such as a lack of public interest in joining the LPS service, socialization has not reached all areas of Balai Gadang Village, operational funds, facilities, and infrastructure are still limited, supervision is still reactive to public complaints, and delays in waste transportation, therefore important steps are needed for improvement and sustainability of the program.